PENGARUH PERBANDINGAN PUREE LABU KUNING (Cucurbita moschata ex. Poir) DAN TAPIOKA TERHADAP KARAKTERISTIK BIKA AMBON - Tristya Zumrotin, Hindun; Sugitha, I Made; Indri Hapsari A., Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
This study aims to determine the effect of the puree pumpkin and tapioca comparison on the characteristics of bika ambon and to determine the right ratio of it to produce of the best characteristics. The experimental design used was completely randomized design (CRD) by treatment with puree pumpkin and tapioca as follows : 0%:100%, 20%:80%, 40%:60%, 60%:40%, 80%:20%. Each treatment was repeated three times to obtain 15 experimental units. The results showed that the treatment was significant effected to water, protein, fat, carbohydrate, and beta carotene contens includes sensory evaluation (colour, texture, and overall acceptance) of bika ambon. Except for the ash content, aroma, cavity cake, and flavor. The best characteristic of bika ambon (38.71% water, 0.76% ash, 5.05% protein, 14.05% fat, 41.43% carbohydrate, 4.65 mg/100g beta carotene contens, 5.55 color (like), 5.70 aroma (like), 5.30 texture (rather like), 3.80 cavity cake (hollows), 6.15 flavor (like) and 5.85 overall acceptance (like)) was produced by ratio of 40% puree pumpkin and 60% tapioca.
Keywords: puree pumpkin, tapioca, bika ambon